Executive Function, Theory of Mind, and Conduct-Problem Symptoms in Middle Childhood - Austin, Gina; Bondü, Rebecca; Elsner, Birgit (Frontiers in Psychology, 2020)
Studies show relations between executive function (EF), Theory of Mind (ToM), and conduct-problem (CP) symptoms. However, many studies have involved cross-sectional data, small clinical samples, pre-school children, and/or did not consider potential mediation effects. The present study examined the longitudinal relations between EF, ToM abilities, and CP symptoms in a population-based sample of 1,657 children between 6 and 11 years (T1: M=8.3 years, T2: M=9.1 years; 51.9% girls). We assessed EF skills and ToM abilities via computerized tasks at first measurement (T1), CP symptoms were rated via parent questionnaires at T1 and approximately 1 year later (T2). Structural-equation models showed a negative relation between T1 EF and T2 CP symptoms even when controlling for attention-deficit hyperactivity disorder symptoms and other variables. This relation was fully mediated by T1 ToM abilities. The study shows how children’s abilities to control their thoughts and behaviors and to understand others’ mental states interact in the development of CP symptoms.